2020
DOI: 10.1101/2020.08.04.20168351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Effective Reproduction Number for COVID-19 in Bangladesh and its districts

Abstract: Background Bangladesh is going through an unprecedented crisis since the onset of the COVID-19 pandemic. Throughout the COVID-19 pandemic, the reproduction number of COVID-19 swarmed in the scientific community and public media due to its simplicity in explaining an infectious disease dynamic. This paper aims to estimate the effective reproduction number (Rt) for COVID-19 over time in Bangladesh and its districts using reported cases. Methods Adapted methods derived from Bettencourt and Ribeiro (2008), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The estimate showed that as of May 7th, 2020, Nigeria needs to re-evaluate their control measures as R t was above one. The Bangladesh estimate also shows a similar pattern [70]. For this approach, we let L(t) be locally acquired infections and λ(t) be the rate of infection.…”
Section: Statistical Modellingmentioning
confidence: 80%
See 2 more Smart Citations
“…The estimate showed that as of May 7th, 2020, Nigeria needs to re-evaluate their control measures as R t was above one. The Bangladesh estimate also shows a similar pattern [70]. For this approach, we let L(t) be locally acquired infections and λ(t) be the rate of infection.…”
Section: Statistical Modellingmentioning
confidence: 80%
“…We present below the R-syntax for computing and plotting the marginal posterior probabilities of 𝜃 and finding its 95% HPD intervals. (70,190, 0.01) # set possible range of theta tau = seq(0.0001, 1, 0.01) # set possible range of tau # 2D lattice of theta and tau par1 = matrix(theta,length(theta),length(tau)) par2 = matrix(tau, length(theta),length(tau)) log_prior = -log(par2) # log prior density…”
Section: Application Of Bayesian Statistics To Real-life Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the transmission of COVID-19, many studies used a reproduction number of the coronavirus as an indicator of the disease's ability to spread in both the early phase and the real-time [7][8][9][10][11][12][13][14][15][16]. A basic reproduction number (R 0 ) is an indicator whether a disease will become an outbreak or not [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh has been battling with this disease since 8th March 2020 when the first 3 cases were reported and since then COVID-19 has spread in almost all the districts resulting in a nationwide lockdown from the 17 th March which has not yet been completely lifted (Hridoy et al, 2020b). As of 21st July 2020, the mean reproduction number of SARS-CoV-2 in Bangladesh is 1.32 (Hridoy et al, 2020a) and as of 31st August 2020, there have officially been 312,996 cases and 4,281 deaths due to COVID-19 in this country (Bangladesh Coronavirus-Worldometer, 2020). With the existing health policy and structures, battling COVID-19 has been a mammoth task for Bangladesh and people are still facing obstacles to ensure appropriate treatment for themselves (Khan et al, 2020;Shammi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%